Effects of Student’s Grade to Teacher’s Teaching: a Case Study in an Indigenous Classroom - Sianturi, Murni; Lin, Huei-Hsuan (Journal of Education and Vocational Research, 2017)
Abstract: The perspective of teaching in rural area led this study to investigate non-indigenous teacher’s teachings in an indigenous classroom of one of rural elementary schools in Hualien, Taiwan. The teacher’s views on indigenous students’ grade and how it related to the teacherâ€™s teaching were explored also. This study was a case study. Data was collected and analyzed by applying qualitative method. It implemented classroom ethnography approach. It revealed that although the teacher had demonstrated a great deal of passion in teaching indigenous students, involvement the students in some indoor and outdoor activities, and using various media to get studentsâ€™ attention, but he was concerned about his studentsâ€™ low academic achievement. In Hualien, there are annual provincial examinations on the subjects of Chinese, Mathematics and English in May, which all the elementary students are required to take. To improve the student academic performance he used some classroom time to practice drills rather than spending time on exploratory activities. When indigenous students’ underperformance in standardized tests are considered as reflecting poor quality of teaching, preparing students for the sit-in tests will continue to be a part of classroom teaching. This study suggests that teachers have to understand the educational context in which teaching and learning take place. Knowing this would provide teachers a more meaningful teaching and learning. Keywords: Teaching, grade, non-indigenous teacher, indigenous students, rural elementary school